PENGARUH KONEKSI POLITIK DAN STRUKTUR KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study raises the issue of the influence of political connections and managerial ownership structures on firm value based on the phenomenon of political connection practices that occur in manufacturing companies in Indonesia. This study aims to analyze and obtain empirical evidence of the influence of political connections and managerial ownership structures on the value of the company where the long-term goals of the formation of companies to maximize the value of the company by increasing the prosperity of the owner or shareholders. This research sample uses secondary data derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. Samples were taken using purposive sampling and that met the sample selection criteria. The sample used was 87 companies. Data is processed with Eviews 9 software using the General Least Square (GLS) method. The results of the study show that political connections have a positive positive effect on company value. While the managerial ownership structure does not have a significant effect on firm value.